1999
DOI: 10.1677/erc.0.0060025
|View full text |Cite
|
Sign up to set email alerts
|

Clinical studies of apoptosis and proliferation in breast cancer.

Abstract: The interaction between cell death and cell proliferation determines the growth dynamics of all tissues. Studies are described here which relate the changes in proliferation and apoptosis that occur in human breast cancer during medical therapeutic manoeuvres. Xenograft studies strongly support the involvement of increased apoptosis as well as decreased proliferation after oestrogen withdrawal, and limited studies in clinical samples confirm the involvement of both processes. Cytotoxic chemotherapy induces inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 9 publications
2
28
0
Order By: Relevance
“…Inducing apoptosis is an important strategy to overcome cancer [36,37,38]. Previous studies proved that activations of caspase-9 and caspase-3 lead to apoptosis in FaDu cells [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Inducing apoptosis is an important strategy to overcome cancer [36,37,38]. Previous studies proved that activations of caspase-9 and caspase-3 lead to apoptosis in FaDu cells [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of apoptosis and decreased proliferation are factors in the biological response of breast cancer to chemotherapy and endocrine therapy (Dowsett et al, 1999) and, therefore, defects in their regulatory machinery could relate to poor Survivin as a marker of poor prognosis in breast cancer AR Hinnis et al response. As well as examining proteins more extensively studied, such as p53, bcl-2, bax and p21, the phosphorylation status of p53, Chk2 and the IAP family members survivin and XIAP were considered.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 A series of studies on animal models and clinical cancer specimens have demonstrated that apoptosis plays an important role in the genesis and development of malignancies and appears to be a critical approach through which endocrine therapy, radiotherapy, chemotherapy and molecular targeting therapy with trastuzumab exert their biological effects. [12][13][14][15][16][17][18][19][43][44][45][46][47][48] It was reported that cyclophosphamide treatment of mice bearing the murine mammary adenocarcinoma MCa-4 increased the apoptotic index from 2.5% at baseline to more than 20% after treatment. 13 Similar results were also found after treatment with cisplatin, doxorubicin and ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%